1989
DOI: 10.1248/cpb.37.3050
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers from marine invertebrates. X. Mode of action of an antibacterial glycoprotein, aplysianin E, from eggs of a sea hare, Aplysia kurodai.

Abstract: An antibacterial factor, aplysianin E, was purified from the eggs of a sea hare, Aplysia kurodai. Purified aplysianin E was a glycoprotein of 250 kilo daltons consisting of 3 subunits, and showed both antibacterial and antineoplastic activities. The two activities were lost in parallel on heating and at low and high pH. This factor was half-maximally active for gram-positive and -negative bacteria at 0.12-3.3 micrograms/ml and its action was not bactericidal but bacteriostatic. Aplysianin E did not induce morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Unlike previous reports of similar proteins isolated from sea hares (Kisugi et al, 1989;Yamazaki et al, 1990;Melo et al, 1998Melo et al, , 2000, we demonstrate that substrates determined the bactericidal or bacteriostatic effects of escapin. Bacteria cultured in M9 and glucose medium without high levels (50·mmol·l -1 ) of selected amino acids or without Tryptone Peptone supplements were not killed (Figs·7, 8).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous reports of similar proteins isolated from sea hares (Kisugi et al, 1989;Yamazaki et al, 1990;Melo et al, 1998Melo et al, , 2000, we demonstrate that substrates determined the bactericidal or bacteriostatic effects of escapin. Bacteria cultured in M9 and glucose medium without high levels (50·mmol·l -1 ) of selected amino acids or without Tryptone Peptone supplements were not killed (Figs·7, 8).…”
Section: Discussioncontrasting
confidence: 99%
“…The existence of persister cells in our cultures of E. coli may explain why several sea hare homologues of escapin, including aplysianin-E (Kisugi et al, 1989), aplysianin-P (Yamazaki et al, 1990) and dactylomelin-P isolated from purple fluid of Aplysia dactylomela (Melo et al, 2000), have been characterized as bacteriostatic and not bactericidal, whereas we found escapin to be bactericidal. To test this idea, we extracted and purified dactylomelin-P from Aplysia dactylomela and found that it was also bactericidal under our assay conditions; K.-C. Ko and H. Yong, unpublished data).…”
Section: Discussionmentioning
confidence: 68%
“…The mode of action of an antibacterial glycoprotein was designated and studied by Kisugi et al [16] ,i.e. aplysianin E against a range of bacteria.…”
Section: Aplysianin Ementioning
confidence: 99%
“…In addition, there was no apparent decrease in turbidity (data not shown), suggesting that aplysianin-A has no bacteriolytic activity. These facts indicate that aplysianin-A was ~c~ ~~~~laxgm~llg~~ so not bacteriocidal, but bacteriostatic like aplysianin-E, an antibacterial glycoprotein in the egg mass of A. kurodai [1,17].…”
Section: <___mentioning
confidence: 95%